Digital heritage and archaeology in practice : data, ethics, and professionalism - Watrall, Ethan; Goldstein, Lynne (Book collections on Project MUSE., 2022)
This text brings together archaeologists and heritage professionals to discuss practical applications of digital and computational approaches to the field. Contributors explore the diverse and exciting ways in which digital methods are being deployed in archaeological interpretation and analysis, museum collections and archives, and community engagement.